The actual use of ERP systems in the financial management of enterprises in Vietnam - Th. H. Pham (Вестник университета, 2021)
The article considers theoretical issues and problems of practical application of the Enterprise Resource Planning System (ERP) as the basis of financial management for companies in Vietnam. The introduction of the ERP system improves the quality of information and supports analysis the management of the company, contributes to the organization of a financial management based on an innovative and long-term perspective, and increase the efficiency of the system as a whole. The article analyses the using of the ERP system in the process of enterprise management, lists the most famous domestic and foreign ERP systems, compares existing systems in Vietnam today, indicates the difficulties in deploying in the company. Solutions for the development of the ERP system are proposed